Features of the regional identity of the Crimean population - Fisenko, Olga (2020)
The article discusses the issues of local identity. The article discusses the issues of local identity. The author proves the influence on the formation of regional identity of the territorial location of the region that organically combines Eastern Christian, Islamic, and Western Christian civilizations. The author proves the influence on the formation of regional identity of the territorial location of the region that organically combines Eastern Christian, Islamic, and Western Christian civilizations.